2008
DOI: 10.1590/s0100-736x2008001000008
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação experimental por Ipomoea asarifolia (Convolvulaceae) em caprinos e ovinos

Abstract: Ipomoea asarifolia causa uma síndrome tremorgênica em ovinos, caprinos, bovinos e búfalos. Este experimento teve como objetivos determinar a toxicidade para caprinos de I. asarifolia verde, colhidas nas épocas de chuva e de estiagem, e da planta seca triturada, determinar a toxicidade da planta para ovinos, e determinar se o princípio ativo da planta é eliminado pelo leite em doses tóxicas para os cordeiros. No primeiro experimento a planta fresca colhida na época de estiagem e na época de chuvas foi administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 4 publications
(10 reference statements)
0
27
1
13
Order By: Relevance
“…Segundo Tokarnia et al (2000) e Araújo et al (2008) a planta é menos tóxica no período das chuvas e causa intoxicação com a folha verde ou seca. Os tremores, relatados por todos os entrevistados, foram o principal sinal clínico, sendo que estes desaparecem quando os animais deixam de ingerir a planta.…”
Section: Discussão E Conclusõesunclassified
See 1 more Smart Citation
“…Segundo Tokarnia et al (2000) e Araújo et al (2008) a planta é menos tóxica no período das chuvas e causa intoxicação com a folha verde ou seca. Os tremores, relatados por todos os entrevistados, foram o principal sinal clínico, sendo que estes desaparecem quando os animais deixam de ingerir a planta.…”
Section: Discussão E Conclusõesunclassified
“…O tratamento é a retirada do animal do local onde ocorre a salsa. O relato de que os cordeiros lactentes são afetados através do leite, não foi comprovado experimentalmente (Araújo et al 2008), entretanto, há evidências de que a toxina da planta seja eliminada através do leite . Deve ser feito o diagnóstico diferencial com outras plantas que afetam o sistema nervoso, principalmente Ipomoea carnea que, apesar de encontrada na região, não foi relatada como tóxica.…”
Section: Discussão E Conclusõesunclassified
“…Emediato et al (2009a) also observed weight gains for Bergamácia ewes 60 days after postpartum, regardless of the inclusion of PF in the concentrate. For lactating ewes, weight loss is attributed to the difficulty in providing nutrients for feeding in amounts suitable for the matrices during this phase, since the energy demand increases more rapidly than the dry matter intake; therefore, the ewes use energy reservations to produce milk and stop accumulating body mass (Araújo et al, 2008).…”
Section: Coefficient Of Variation In Plots (Supplement)mentioning
confidence: 99%
“…Behaviour changes without tremors were also observed in weaned of mice ingesting I. asarifolia (Lopes et al 2014). In sheep the poisoning has been observed in nursing lambs that remain confined, without ingesting the plant, while their mothers ingested the plant while grazing without showing signs of disease (Araújo et al 2008, Freitas et al 2011). These observations suggest that the tremorgenic compound of the plant is eliminated in milk.…”
Section: Introductionmentioning
confidence: 95%
“…These observations suggest that the tremorgenic compound of the plant is eliminated in milk. However, this hypothesis was not confirmed in experiments in sheep (Araújo et al 2008) and goats (Freitas et al 2011) that ingested I. asarifolia before and/or after lambing without causing clinical signs in the offspring.…”
Section: Introductionmentioning
confidence: 96%